PERCEPTIONS OF COUNSELING AND MEDITATIONS IN DIVORCE EXPERIENCE: FROM LAWYERS, COUNSELORS AND LEGAL AID CLIENTS (PERAK, MALAYSIA) - S. Annie Margaret; Zawawi Abu Bakar; Siti Rozaina Binti Kamsani (Jurnal Penyelidikan Sains Sosial, 2021)
Divorce is one of the most challenging parts of anyone’s life once divorce occurs, the couples will have to make themselves ready to go to the divorce proceedings. In fact, for many couples, even contacting a matrimonial lawyer and seeking counselling is a set of new experiences.Unfortunately, the poor service during the reconciliation process, together with inherently destructive problems, made their marriage irretrievably broken down, and the only available option left was to divorce At this point together with their emotional rollercoaster they attend mediation The purpose of this paper is to describe included in-depth interviews the results of a study of 14 clients of the Legal Aid Department spouses who were divorced between 2017 till 2018 and were the individuals who open a divorce on the ground that the marriage has irretrievably broken down under section 54 of the Law Reform Marriage Act, 1976. The present research outlines that even though the law designed a provisions to encourage reconciliation yet experiences over the counseling divorce process have also been align with other well-known researchers like Mimi Kamariah, Nora Abdul Hak, Noraini Hashim, Nur Ezan Rahmat, Najibah Md. Zain, and Sarafuddin Abdul Syahid Sowell . Poor service during the reconciliation process, together with inherently destructive problems, made their marriage irretrievably broken down, and the only available option left was to divorce. Even though this was not the best option, this seems the only option to end this wretchedly unhappy marriage